2014
DOI: 10.1177/1044207313514609
|View full text |Cite
|
Sign up to set email alerts
|

Navigating University Policies to Support Postsecondary Education Programs for Students With Intellectual Disabilities

Abstract: Postsecondary education (PSE; that is, a college degree or advanced training from a technical school) is a necessary credential for many high-skilled and well-paying jobs (Strauss & Howe, 2005;Thoma et al., 2011). For some populations of young adults, however, access to PSE has not been an option. Consequently, institutions of higher education (IHEs) are putting forth efforts to maximize diversity and increase educational opportunities for students from historically underserved populations (Higbee, 2009). Trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…It is important to understand the individualized nature of the programs allow programs to make adjustments on the level of rigor to maximize student growth. In our experience, we have witnessed students with IDD achieve success in college courses with no modifications to assignments; however, since PSE programs are nondegree programs due to the nature of college admission (Plotner and Marshall, 2014), the potential discussions regarding PSE certification programs acting as a formal transition or bridge program to credit bearing degree programs has been neutralized. Future research should examine these ideas further.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the individualized nature of the programs allow programs to make adjustments on the level of rigor to maximize student growth. In our experience, we have witnessed students with IDD achieve success in college courses with no modifications to assignments; however, since PSE programs are nondegree programs due to the nature of college admission (Plotner and Marshall, 2014), the potential discussions regarding PSE certification programs acting as a formal transition or bridge program to credit bearing degree programs has been neutralized. Future research should examine these ideas further.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were identified by reviewing studies that reported barriers and supports experienced by new programs and selecting those that appeared in multiple studies (Folk et al, 2012;Getzel, 2008;Hafner et al, 2011;Neubert & Redd, 2008;O'Connor et al, 2012;Plotner & Marshall, 2014;Stodden & Whelley, 2004;Thoma, 2013;Thoma et al, 2011). The survey instrument consisted of four sections and 56 questions used in the analysis.…”
Section: Instrumentmentioning
confidence: 99%
“…Others have summarized challenges faced during program development and provided suggested strategies for negotiating these challenges (Plotner & Marshall, 2014;Thoma et al, 2011). From these descriptions, several areas have been identified as key concerns that emerge as new PSE programs are proposed and implemented in college settings.…”
Section: Introductionmentioning
confidence: 97%
“…Although the idea of inclusive higher education through PSE programs for students with IDDs is not new (Neubert, Grigal, Moon, & Redd, ), the numbers of such programs have greatly increased in recent years (Weir, Grigal, Hart, & Boyle, ). Rather than granting traditional degrees, PSE programs often provide services and supports to help students with IDDs have an opportunity to work toward life goals in PSE setting (Grigal, Hart, & Weir, ; Papay & Bambara, ; Plotner & Marshall, ). In the same manner that traditional matriculating students engage in PSE to improve employment outcomes, many PSE programs provide opportunities for students with IDDs to develop skills that increase their employability (Grigal et al, ; Papay & Bambara, ).…”
Section: Introductionmentioning
confidence: 99%